Sosialisasi Peran Pendidikan Lingkungan Dalam Membangun Kesadaran Dan Partisipasi Siswa/Siswi Sejak Usia Dini - Zahra Zamaya; Raisyah S.M. Rimosan; Siti Damayanti; Marsye M.L. Runtuwene; Alda Aghata Iza Zafira; Rietma Danti Ayuningtyas; Hidayat Chusnul Chotimah (CV. Multi Kreasi Media, 2024)
Environmental education is one of the efforts aimed at preserving the surrounding environment so as not to harm humans and other living things. Efforts to preserve the environment need to be carried out early on so that awareness and habits of the importance of nature for humans can be instilled and threats to human security can be reduced, which include seven aspects, namely economic, food, health, environmental, personal, community, and political security. To realize this, the Yogyakarta Technology University community service team is trying to conduct socialization with kindergarten students to help them realize one aspect of human security, especially environmental security. This activity has encouraged the enthusiasm of students at the kindergarten level to learn outside the classroom while preserving the surrounding environment.